PEMBERDAYAAN EKONOMI MASYARAKAT NELAYAN MELALUI DIVERSIFIKASI PRODUK OLAHAN HASIL LAUT SEBAGAI STRATEGI PENGENTASAN KEMISKINAN DI DESA LALONGGASUMEETO KABUPATEN KONAWE - Rostin Rostin; Muhammad Yani Balaka; Heppi Millia; Wali Aya Rumbia; Yohanes Boni; Lapipi Lapipi; Andriani Puspitaningsih; Fitria Lapau; Yohanes Sugiyanta (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
Fishing communities in Lalonggasumeeto Village, Konawe Regency, Southeast Sulawesi, face low value-added fishery products, seasonal income fluctuations, and limited business diversification. This Internal Community Partnership Program (PKMI) aimed to strengthen the economic capacity of fishing households through diversification of locally based seafood products. The program applied the Participatory Rural Appraisal (PRA) and learning by doing approaches, covering homemade fish nugget production, standard operating procedures and hygiene, appropriate equipment, branding and packaging, business legalization, business management and cost of production (COP) training, digital marketing, and institutional strengthening. The program improved participants’ production skills, hygiene awareness, business management, digital marketing knowledge, and entrepreneurial motivation. Homemade Fish Nuggets achieved a production cost of IDR 34,000 per 500-gram package and a selling price of IDR 45,000–50,000, with an estimated monthly profit of approximately IDR 8,000,000 at a production capacity of 20 packages per day. The program demonstrates that seafood product diversification is an effective strategy for increasing value added and improving the economic resilience of fishing households.